Policy Communication Analysis of the Criminal Investigation Unit in Corruption Prevention in Central Tapanuli Regency - Cuanda Mitra Perdana; Hasan Sazali; Fakhrur Rozi (DAWUH : Islamic Communication Journal, 2026)
This study examines the implementation and effectiveness of communication policy by the Criminal Investigation Unit (Sat Reskrim) of the Central Tapanuli Police in preventing corruption. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document analysis involving police officers, government officials, and community members. The study is supported by communication theory, particularly Negative Dominance Theory, to analyze how messages are constructed and influence public perception and behavior. The findings indicate that the communication policy is implemented through preventive, educative, and coordinative strategies, emphasizing persuasive, educative, and informative communication approaches. These strategies are delivered through direct interactions such as socialization, legal counseling, and community discussions, as well as through digital platforms like social media. The use of negative messages highlighting legal consequences, combined with positive messages promoting transparency and integrity, effectively increases public awareness and discourages corrupt behavior. Moreover, communication is carried out in a humanistic and participatory manner, fostering trust, openness, and collaboration between the police and the community. The effectiveness of this policy is supported by several factors, including leadership commitment, strong team coordination, adequate communication facilities, inter-agency collaboration, and increasing community participation. However, challenges such as limited infrastructure, varying levels of public awareness, and bureaucratic constraints still affect implementation. In conclusion, the communication policy of Sat Reskrim Polres Tapanuli Tengah significantly contributes to corruption prevention by strengthening public awareness, participation, and accountability. The integration of strategic communication and community engagement supports the development of a sustainable anti-corruption culture and enhances transparent and accountable governance.